1999
DOI: 10.1103/physreva.59.267
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime measurement ofHeusing an electrostatic ion trap

Abstract: The lifetimes of the metastable 1s2s2 p 4 P 5/2 level of He Ϫ , as well as the lifetime of the average of the 4 P 3/2 and 4 P 1/2 levels, have been measured using a new type of ion trap that stores keV ion beams using electrostatic fields only. The use of a pure electrostatic field avoids the complication of magnetic-field-induced mixing effects, which can interfere with the measurement of the spontaneous decay. The measured lifetime for the 4 P 5/2 state, after correction for decay induced by blackbody radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 20 publications
4
25
0
Order By: Relevance
“…Most significantly, there is a large suppression of the total He − signal, which is attributed to electron transfer to SF 6 . However, it is also found that the He − produced at the two lower energy resonances (22 and 23 eV) is more strongly affected by the addition of SF 6 than that at the high energy resonance (25 eV).…”
Section: Effect Of the Electronic State Of He −mentioning
confidence: 99%
See 4 more Smart Citations
“…Most significantly, there is a large suppression of the total He − signal, which is attributed to electron transfer to SF 6 . However, it is also found that the He − produced at the two lower energy resonances (22 and 23 eV) is more strongly affected by the addition of SF 6 than that at the high energy resonance (25 eV).…”
Section: Effect Of the Electronic State Of He −mentioning
confidence: 99%
“…The primary anionic product detected in the gas phase by mass spectrometry is the SF 5 − fragment. Figure 5 shows how the He − ion yield is affected by addition of SF 6 . Some preliminary data of this type were briefly presented in Ref.…”
Section: Effect Of the Electronic State Of He −mentioning
confidence: 99%
See 3 more Smart Citations